2020
DOI: 10.3389/fimmu.2020.01135
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Human Monoclonal Antibodies Against Adeno-Associated Virus From Donors With Pre-existing Immunity

Abstract: With the advent of single B-cell cloning technology, we can isolate antibodies against virtually any antigen to study the interaction of a given pathogen with the immune system and develop novel therapeutic strategies. Antibodies directed against the capsid of adeno-associated viruses (AAV) are a significant obstacle to effectively leveraging AAV as a gene-delivery vector in seropositive individuals. In order to design next-generation vectors that can evade neutralization by these antibodies, studies have mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The AAV antibody prevalence is similar in people with and without HIV and is similar to the prevalence in NHPs. AAV9 is one of the serotypes with the lowest frequency of pre-existing antibodies in the human population with ~33.5% of people with an AAV9 nAb titer [ 18 , 19 ]. In our studies, increases in anti-AAV9 neutralizing antibodies were observed in the highest dosing groups (Group 3, 4) at 6 months following EBT-001 administration.…”
Section: Discussionmentioning
confidence: 99%
“…The AAV antibody prevalence is similar in people with and without HIV and is similar to the prevalence in NHPs. AAV9 is one of the serotypes with the lowest frequency of pre-existing antibodies in the human population with ~33.5% of people with an AAV9 nAb titer [ 18 , 19 ]. In our studies, increases in anti-AAV9 neutralizing antibodies were observed in the highest dosing groups (Group 3, 4) at 6 months following EBT-001 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already addressed the former obstacle by minimizing toxicity, while the latter, though interestingly preserved when delivered with a viral vector, posed another challenge with regard to AAV-mediated efficiency. As thoroughly discussed in the results, there are possibilities that viral vector-mediated approaches could be rendered ineffective due to preexisting humoral immunity ( Giles et al, 2020 ). It is complicated since the full extent of such an immune response may not be fully reflected in in vivo studies employing DMD models as noted by Chicoine et al (2014b) .…”
Section: Resultsmentioning
confidence: 99%
“…The neutralizing mAb available are all from animal models. Human mAb have been isolated, but all to-date are binding, not neutralizing, and attempts at structural epitope mapping have not yet succeeded (Giles et al, 2020). Notwithstanding that studies of mAb-binding might not be fully representative of polyclonal neutralization mechanisms (Dudek et al, 2020a), this study focuses on the mAb for which epitopes can be mapped structurally.…”
Section: Aav Antibody Complexesmentioning
confidence: 99%